Capital wars : the new east-west challenge for entrepreneurial leadership and economic success - Pinto, Daniel (London : Bloomsbury, 2014)
'Just a few years is all it took for the debt crisis to bring down the mighty forces of American and European capitalism and undo two centuries of Western dominance on the world's economic and political stage. In Capital Wars, Daniel Pinto offers a unique insight into how the East is winning the battle for economic supremacy, thereby shaping the new world order and leaving America and Europe with no choice but to reinvent themselves. Drawing on his own experience at the highest levels of business and finance, Pinto dismisses the common notion that globalization is to blame for anemic growth, massive unemployment and over-indebtedness. Instead, he argues that by killing our own entrepreneurial spirit, we have set the stage for the demise of the West and the rise of emerging powers. Capital Wars is a road map designed to re-energize large corporations, better control financial markets and reposition the entrepreneur at the center of the Western capitalist model in order to regain economic dominance.' -- Publisher's website.
From the capitalism of creators to the capitalism of apparatchiks : the rise and fall of the West. The end of our illusions -- The impossible gamble of redistribution without growth -- From empire-builders to administrators : chronicle of a death foretold -- Their conquests, our recipes : how emerging powers made our entrepreneurial capitalism their own. Emerging powers : how the war was (almost) won -- How we were robbed of our own capitalism -- The new geopolitics of money -- Rebuilding upon the ruins of Western capitalism. First step : bring down the myths -- Turning the apparatchik CEO back into a real entrepreneur -- Transforming finance from an end to a means -- Repositioning the business-creator as the cornerstone of capitalism -- Conclusion : reinvent the magic triangle.
'First published in France in 2013 by Odile Jacob as Le choc des capitalismes : comment nous avons d{u2970}oss de notre g{u296E}ie entrepreneurial et comment le r{u2969}nventer.
Includes bibliographical references and index.
Keywords: Entrepreneurship -- Western countries; Capitalism -- History -- 21st century; Globalization -- Economic aspects; Global Financial Crisis, 2008-2009.; Financial crises -- History -- 21st century; Western countries -- Economic conditions